The role of trees for sustainable management of less-favored lands: the case of eucalyptus in Ethiopia - Jagger, Pamela; Pender, John L. (Elsevier, 2003)
In recent years the planting of eucalyptus trees in Ethiopia has expanded from State owned plantations to community woodlots and household compounds.... The regional government promotes planting of eucalyptus and other species in community woodlots, and has recently begun to allow private planting of eucalyptus on community wasteland and steep hillsides. In this paper, the authors review the debate about the ecological impacts of eucalyptus trees, as well as the economic factors that influence whether smallholders invest in these trees. Ex ante benefit-cost analysis based on community level survey data from Tigray illustrates that under most conditions planting eucalyptus trees yields high rates of return, well above 20% under most circumstances. The effect of variable harvest rates, the costs of decreased crop production when eucalyptus trees are planted on farmlands, and differences between administrative zones are considered relative to our base case in our rate of return estimates. The importance of fast growing tree species that can accommodate the high discount rates associated with smallholders in this region is emphasized.